ANALISIS OBYEK DAYA TARIK WISATA (ODTW) DAN INTERPRETASI JALUR EKOWISATA ELEPHANT TOUR DI PUSAT LATIHAN GAJAH TAMAN NASIONAL WAY KAMBAS - Miftahudin Miftahudin; Gunardi Djoko Winarno; Trio Santoso; Arief Darmawan (Jurnal Hutan Tropis, 2021)
Way Kambas National Park is famous as an endemic habitat for the Sumatran Elephant (Elephas maximus sumatranus) precisely in the Elephant Training Center area as a base for ecotourism activities. Statistics on the number of tourist visits turned out to show a decrease, therefore we need an innovative eco-tourism breakthrough one of which has the potential to be developed is the Elephant Tour ecotourism. The purpose of this study is to identify potential attraction objects that exist in the Way Kambas National Park Elephant Training Center and interpret ecotourism path plans. The method used in this study is field observations to obtain data on potential points and ecotourism path. The data that has been obtained is then tabulated for descriptive and spatial analysis. The results showed that the object of attraction in the Way Kambas National Park precisely in the area of the Elephant Training Center consists of flora, fauna, beauty landscape and planned ecotourism path into two, long and short trips.